Articles You Might Have Missed - Ryan Fuchs; Brian Gooley; Arthur Jurao (Journal of Medical Toxicology, 2023)

Chronic nutrient enrichment increases prevalence and severity of coral disease and bleaching - Rebecca L. Vega Thurber; Deron E. Burkepile; Corinne Fuchs; Andrew A. Shantz; Ryan McMinds; Jesse R. Zaneveld (Global Change Biology, 2014)
Nutrient loading is one of the strongest drivers of marine habitat degradation. Yet, the link between nutrients and disease epizootics in marine organisms is often tenuous and supported only by correlative data. Here, we present experimental evidence that chronic nutrient exposure leads to increases in both disease prevalence and severity and coral bleaching in scleractinian corals, the major habitat‐forming organisms in tropical reefs. Over 3 years, from June 2009 to June 2012, we continuously exposed areas of a coral reef to elevated levels of nitrogen and phosphorus. At the termination of the enrichment, we surveyed over 1200 scleractinian corals for signs of disease or bleaching. Siderastrea siderea corals within enrichment plots had a twofold increase in both the prevalence and severity of disease compared with corals in unenriched control plots. In addition, elevated nutrient loading increased coral bleaching; Agaricia spp. of corals exposed to nutrients suffered a 3.5‐fold increase in bleaching frequency relative to control corals, providing empirical support for a hypothesized link between nutrient loading and bleaching‐induced coral declines. However, 1 year later, after nutrient enrichment had been terminated for 10 months, there were no differences in coral disease or coral bleaching prevalence between the previously enriched and control treatments. Given that our experimental enrichments were well within the ranges of ambient nutrient concentrations found on many degraded reefs worldwide, these data provide strong empirical support to the idea that coastal nutrient loading is one of the major factors contributing to the increasing levels of both coral disease and coral bleaching. Yet, these data also suggest that simple improvements to water quality may be an effective way to mitigate some coral disease epizootics and the corresponding loss of coral cover in the future.